Interaction Between Cecal Metabolites and Liver Lipid Metabolism Pathways During Induced Molting in Laying Hens - Zhang, Jun; Geng, Xiaoqing; Zhang, Yihui; Zhao, Xinlong; Zhang, Pengwei; Sun, Guirong; Li, Wenting; Li, Donghua; Han, Ruili; Li, Guoxi; Tian, Yadong; Liu, Xiaojun; et al. (Frontiers in Physiology, 2022)
Moult is a normal physiological phenomenon in poultry. Induced molting (IM) is the most widely used and economical molting technique. By inducing moult, the laying hens can grow new feathers during the next laying cycle and improve laying performance. However, the lack of energy supply has a huge impact on both the liver and intestines and acts on the intestines and liver through the “gut-liver axis”. More importantly, lipid metabolism in the liver is closely related to the laying performance of laying hens. Therefore, in this study, cecal metabolites and liver transcriptome data during IM of laying hens at the late stage of laying (stop feeding method) were analyzed together to reveal the regulatory mechanism of “gut-liver axis” affecting the laying performance of laying hens from the perspective of lipid metabolism. Transcriptome analysis revealed that 4,796 genes were obtained, among which 2,784 genes had significant differences (p < 0.05). Forty-nine genes were associated with lipid metabolism, and five core genes (AGPAT2, SGPL1, SPTLC1, PISD, and CYP51A1) were identified by WGCNA. Most of these differential genes are enriched in steroid biosynthesis, cholesterol metabolism, drug metabolism—cytochrome P450, synthesis and degradation of ketone bodies, PPAR signaling pathway, and bile secretion. A total of 96 differential metabolites were obtained by correlating them with metabolome data. Induced moult affects laying performance by regulating genes related to lipid metabolism, and the cecal metabolites associated with these genes are likely to regulate the expression of these genes through the “enterohepatic circulation”. This experiment enriched the theoretical basis of induced moult and provided the basis for prolonging the feeding cycle of laying hens.